The Impact of the Mode of Thought in Complex Decisions: Intuitive Decisions are Better - Usher, Marius; Russo, Zohar; Weyers, Mark; Brauner, Ran; Zakay, Dan (Frontiers in Psychology, 2011)
A number of recent studies have reported that decision-quality is enhanced under conditions of inattention or distraction (unconscious-thought; Dijksterhuis, 2004; Dijksterhuis et al., 2006; Dijksterhuis & Nordgren, 2006). These reports have generated considerable controversy, for both experimental (problems of replication) and theoretical reasons (interpretation). Here we report the results of four experiments. The first experiment replicates the unconscious thought effect, under conditions that validate and control the subjective criterion of decision quality. The second and third experiments examine the impact of a mode of thought manipulation (without distraction) on decision quality in immediate decisions. Here we find that intuitive or affective manipulations improve decision quality compared to analytic/deliberation manipulations. The fourth experiment combines the two methods (distraction and mode of thought manipulations) and demonstrates enhanced decision quality, in a situation that attempts to preserve ecological validity. The results are interpreted within a framework that is based on two interacting subsystems of decision-making: an affective/intuition based system and an analytic/deliberation system.